If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -25 = 3x + -15 Reorder the terms: -25 + 2x = 3x + -15 Reorder the terms: -25 + 2x = -15 + 3x Solving -25 + 2x = -15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -25 + 2x + -3x = -15 + 3x + -3x Combine like terms: 2x + -3x = -1x -25 + -1x = -15 + 3x + -3x Combine like terms: 3x + -3x = 0 -25 + -1x = -15 + 0 -25 + -1x = -15 Add '25' to each side of the equation. -25 + 25 + -1x = -15 + 25 Combine like terms: -25 + 25 = 0 0 + -1x = -15 + 25 -1x = -15 + 25 Combine like terms: -15 + 25 = 10 -1x = 10 Divide each side by '-1'. x = -10 Simplifying x = -10
| 2m+5=50 | | -2[1-5(1+4x)]=-108-10x | | 2(m-5)=50 | | f(-4)=-5x-3 | | 0.2(x-2)=5.2 | | 2/3-9m+12 | | 9x-26=-58+x | | 8(x+4)+x=2(x+3)-8 | | (4D^3-7D+3)y=0 | | 5x/11-x=3(x-9) | | 0.05x-1.6=0.2(x-5) | | 1/2k+6g=2k | | G*g+5g-35=3G | | 12-2(a-1)+5+a= | | 1/4x-5+x | | G*g+8g=-15 | | -2(x+3)+4=8(x+5)+4 | | 3x-12-2x+3= | | f(x)=2(x)+2 | | (9x^2+3x+1)= | | G*g+7g+30=0 | | 10+7x=5(x)-6 | | 0.7x-0.1(5-x)=3.9 | | 3-2x=5-3x | | x/6x-x^2 | | 18-(g-6)=8g+3(g-4) | | 4x=2(5x+12) | | 3ln(x-7)=15 | | -2a+2+3a=10-26 | | 3/y=11/5 | | 512/8 | | -5(4x-1)+x=-3(x+3) |